Unprecedented stability in Au@Co core-shell bimetallic catalyst supported on SBA-15 (Au@Co/SBA-15) for atmospheric pressure CO hydrogenation. (September 2021) - Jain, P.; Chimote, M.; Vinod, C.P.
Abstract: Bimetallic nanoparticles demonstrating synergistic effect (electronic or geometric modification) often show distinct chemical and physical properties compared with the parent metals. In catalysis, this provides opportunities to engineer solid materials with appreciable activity, selectivity, and stability. In the present study, we have synthesized Au@Co core–shell bimetallic nanoparticles by colloidal synthesis approach with a focus to study and explore the synergistic effect between Au and Co in Au@Co bimetallic catalyst supported on SBA-15 on Fischer Tropsch (FT) reaction. The deactivation of catalyst is a significant drawback in CO hydrogenation (syngas conversion/FT synthesis), and the present study provides the design of a new material, which resists the surface cobalt oxide formation and inactive coke formation and gives efficient CO conversion with high stability. Graphical abstract: Image 1